Optimization of fuel and energy infrastructure for urban ground passenger transport system - D. A. Dryuchin (Вестник СибАДИ)
Introduction. The influence of urban passenger transport on the formation of a comfortable urban environment is indicated. The role and place of the fuel and energy supply infrastructure as one of the subsystems in the urban ground passenger transport system is determined. The results of the review of scientific works in the field of designing the infrastructure of fuel and energy supply are presented. The insufficient degree of development of methodological support forming the integrated development of subsystems of urban passenger transport is noted. The purpose of the study is formulated, the tasks are defined, the solution of which ensures its achievement.Materials and methods. A brief description of the methodology for determining the main technological parameters of the fuel and energy infrastructure of the urban ground passenger transport system is presented. The sequence of use of the presented calculation formulas is determined, the main hypothesis underlying the research is described. The expected results are described.Results. As intermediate results of the conducted research, the data and functional dependencies obtained in the process of performing the research part of the work are presented. These data provide practical implementation of the developed methodology and allow modeling of the parameters of the projected infrastructure. The dependencies obtained as a result of modeling and which are the basis for the development of optimization measures are given. Discussion. It is noted that the logistics approach implemented in the development of the presented methods allows us to determine the design parameters of the fuel and energy infrastructure as one of the subsystems of urban passenger transport, which ensures the coordinated development of the system based on the conditions for achieving maximum efficiency.Conclusion. As a generalizing conclusion, it is noted that the practical implementation of the developed methodology within the framework of an integrated system approach makes it possible to achieve the set goal – to increase the efficiency of the urban ground passenger transport system.